2016
DOI: 10.1186/s13195-016-0225-7
|View full text |Cite
|
Sign up to set email alerts
|

A digital enzyme-linked immunosorbent assay for ultrasensitive measurement of amyloid-β 1–42 peptide in human plasma with utility for studies of Alzheimer’s disease therapeutics

Abstract: BackgroundAmyloid-β 1–42 peptide (Aβ1–42) is associated with plaque formation in the brain of patients with Alzheimer’s disease (AD). Pharmacodynamic studies of AD therapeutics that lower the concentrations of Aβ1–42 in peripheral blood require highly sensitive assays for its measurement. A digital enzyme-linked immunosorbent assay (ELISA) using single molecule array (Simoa) technology has been developed that provides improved sensitivity compared with conventional ELISA methods using the same antibody reagent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(27 citation statements)
references
References 47 publications
1
26
0
Order By: Relevance
“…Recovery of analyte in spiked human plasma ranged between 57% and 95% of the expected value and was dependent on concentration and varied between samples. This observation corroborates results reported by others—using the same technique—for the measurement of amyloid-β 1–42 peptide in human plasma [ 49 ]. A possible explanation for this difference in recovery in the present study could be the presence of HSP70-specific antibodies, which have been reported in human samples [ 43 , 50 , 51 ].…”
Section: Discussionsupporting
confidence: 93%
“…Recovery of analyte in spiked human plasma ranged between 57% and 95% of the expected value and was dependent on concentration and varied between samples. This observation corroborates results reported by others—using the same technique—for the measurement of amyloid-β 1–42 peptide in human plasma [ 49 ]. A possible explanation for this difference in recovery in the present study could be the presence of HSP70-specific antibodies, which have been reported in human samples [ 43 , 50 , 51 ].…”
Section: Discussionsupporting
confidence: 93%
“…Now NfL has been considered as an especially promising biomarker for neurodegeneration because it can be measurable in plasma 33 . Single molecule array (SiMoA) digital immunoassay platform can offer heightened sensitivity by miniaturizing the reaction volume 34 , and several biomarkers indicative of peptide fragmentation and neuronal dysfunction can be accurately quantified in peripheral blood. In our study, we used this Simoa technology to compare the plasma NFL concentrations of AD, aMCI and normal elderly people(their gender, age and education are matched), and found the concentration of plasma NfL in AD group were significantly higher(p < 0.05) than that in aMCI group and normal group.…”
Section: Discussionmentioning
confidence: 99%
“…As of now the most frequently used biomarkers for AD diagnostics are assays for quantification of amyloid beta 42 (Aβ42) or Aβ42/Aβ40; total and phospho-tau in CSF or blood (reviewed in Song et al 2016;Lewczuk et al 2017;Jack et al 2018). Since the senile plaques are made of aggregates mainly consisting of truncated Aβ (Aβ42), development of Aβ42-specific ELISA has improved the specificity of AD diagnostics (Jarrett et al 1993).…”
Section: Protein Based Assays For Diagnostics Of Alzheimer's Diseasementioning
confidence: 99%
“…The ultrasensitive ELISA technique for the detection of serine 396 and serine 404 showed 400-fold and about 1300fold higher sensitivity when compared to standard ELISA test (Hu et al 2002). Introduction of digital, single molecule assays based on Quanterix platform was important milestone, since this assay allows to detect tau protein and Aβ42 as low as picogram per millilitre range in the CSF and blood (Song et al 2016;Motamedi et al 2018). Simultaneous determination of tau Figure 1.…”
Section: Protein Based Assays For Diagnostics Of Alzheimer's Diseasementioning
confidence: 99%